DUGALIMAN : Dukungan Suami dan Keluarga dalam Persiapan Persalinan yang Aman - Hj. Zakiah; Haryono, Ika Avrilina; Nurliani, Siti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The support of husbands and family members in safe childbirth preparation is crucial for pregnant women. Husbands serve as both emotional and physical companions, providing comfort and security during the birthing process. Challenges encountered in community service partnerships related to spousal and familial support in safe childbirth preparation can encompass several aspects. Firstly, a lack of understanding among husbands and family members regarding the childbirth process can result in minimal emotional and physical support. Many husbands do not participate in prenatal education, leaving them unprepared to provide the necessary support. Secondly, cultural norms that limit the husband's role in childbirth can pose challenges. In some communities, there is still a belief that the husband's role is insignificant in childbirth preparation, leading to decreased participation. This can diminish the pregnant woman's self-confidence and create discomfort. Based on the challenges faced by partners, the proposed solution is the creation of engaging informational media to facilitate the dissemination of information to the public, particularly to husbands and family members, in support of safe childbirth preparation, a program referred to as DuGaLiMan. This initiative was implemented in September 2024 at Babirik Community Health Center, Hulu Sungai Utara Regency, South Kalimantan Province. The DuGaLiMan program, which focuses on spousal and familial support in safe childbirth preparation at Babirik Community Health Center, demonstrates its success in achieving its objectives. The program has successfully increased the knowledge and awareness of husbands and family members regarding the importance of their roles during the childbirth process. With appropriate education, they can provide the necessary emotional and physical support to pregnant women, creating a safer and more comfortable environment.